Modeling of a Double Gas Hydrate Particle Ignition; Applied Sciences; Vol. 12, iss. 12 - Gaydukova O. S. Olga Sergeevna; Misyura S. Ya. Sergey Yakovlevich; Razumov D. S. Dmitry Sergeevich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen